S34 Bmpr-ii Deficiency Leads To An Increase In Lung Egg Deposition, Pulmonary Vascular Remodelling And An Abnormal Liver Vasculature In Mice Chronically Infected With S. Mansoni. (10th November 2014) - Crosby, A; Soon, E; Jones, F; Southwood, M; Haghighat, L; Toshner, M; Raine, T; Horan, I; Yang, P; Davenport, A; Moore, S; Wright, P; et al.
Abstract : Rationale and objectives: Schistosomiasis is the world-wide leading cause of pulmonary arterial hypertension (PAH) and is particularly prevalent in developing countries. More than 80% of patients with familial PAH in the western-world have a mutation in bone morphogenetic protein type-II receptor (BMPR-II), which is a member of the transforming growth receptor-beta (TGF-b) superfamily and is important in cell proliferation and differentiation. The aim of the study was to determine if mice with a heterozygous null mutation in BMPR-II are more susceptible to pulmonary vascular remodelling induced by S. mansoni infection, compared with wild-type littermates. Methods: Wild-type (BMPR-II+/+) and BMPR-II heterozygous (BMPR-II+/-) C57/BL6 mice were infected percutaneously with S. mansoni . Seventeen weeks post-infection right ventricular systolic pressure (RVSP), right ventricular hypertrophy (RVH), liver and lung egg counts were measured. Pulmonary vascular remodelling and liver histology were assessed by morphometry, following immunohistochemistry. Lung, liver and serum cytokines were also measured. A macrophage phagocytosis assay and in vivo bead assay were also performed. Measurements and main results: At 17 weeks post-infection there was a significant increase in pulmonary vascular remodelling associated with a significant increase in egg deposition and cytokines in the lung, in BMPR-II+/- mice. Furthermore, there was a positive correlation between lung egg deposition and pulmonary vascular wall thickness. Additionally, there was a significant dilatation of the central hepatic vein in the BMPR-II+/- infected mice compared with the BMPR-II+/+ infected mice. However, no differences in RVSP, RVH or liver egg deposition were found. Conclusions: This study has shown that mice deficient in BMPR-II are more susceptible to pulmonary vascular remodelling induced by S. mansoni which is directly correlated to an increase in egg burden in these mice. Additionally, we have shown that BMPR-II+/- mice have an abnormal liver vasculature, which may be responsible for increased egg shunting into the lungs.